ESA COMBINED WITH PICTURES TO IMPROVE STUDENTS’ WRITING SKILL IN SMAN 1 KINTAMANI - Ni Made Andriastini; A.A. Istri Yudhi Pramawati (Academic Journal on English Studies (AJOES), 2021)
Writing is a difficult language skill since the students should pay attention to the writing’s aspects and need to express their own ideas. The tenth-grade students of SMAN 1 Kintamani found some difficulties in writing in which they were hard in generating their ideas, how to begin their text, and how to construct a well-structured text. The objective of the present classroom action research was to figure out whether or not writing skill of tenth-grade students of SMAN 1 Kintamani in academic year 2020/2021 can be improved through ESA combined with picture. The undertaking of this research was based on the preliminary study. The pre-test was carried out, and it showed the subjects’ writing skill was low. Therefore, the present study was conducted by implementing ESA combined with picture in two cycles. The result of post-test in each cycle showed that there were significant improvements on the subjects’ writing skill after the application of ESA combined with picture. Furthermore, the questionnaire proved that the subjects’ responses towards the application of ESA combined with picture were positive during the teaching and learning process. In conclusion, the study showed that writing skill of the tenth-grade students of SMAN 1 Kintamani in academic year 2020/2021 can be improved through ESA combined with picture.